A boost for south–south collaboration - Cabrerizo, Franco Martín (2023)
Nature CorrespondenceA boost forsouth–south collaborationFranco M. Cabrerizo A modeltraining initiative to offset the shortage of practical laboratory skills amongyoung scientists from South and Central America could be used to helpstrengthen scientific capacity in the global south. This training was providedby a summer school last month at the Higher University of San Andrés inBolivia, set up by members of the Young Affiliates Network of the World Academyof Sciences (see go.nature.com/3zxnaxg).Thisnetwork consists of around 400 young scientists from more than 80 developingcountries (https://tyan.twas.org), of whom 100 attended the school’s firstcourses. The five instructors — I was one— came from Bolivia, Brazil, CostaRica and Argentina, and passed on skills they had themselves acquired in topinternational labs.We providedhands-on training in key areas of the chemical and biological sciences. Forexample, participants learnt about spectroscopy for studying biologicalmolecules, the potential of using model organisms in research on developmentalbiology, and genetic analysis to investigate plant reproduction. They alsoexplored photochemical reactions and learnt how to set up statisticallyrigorous assays of biochemical activity.Oursouth–south initiative equipped trainees with the tools to further theirresearch. Now more investment in research is needed so that they can applythese tools effectively.Nature 616, 249 (2023)doi:https://doi.org/10.1038/d41586-023-01003-2